WAYS TO ENHANCE INTELLECTUAL POTENTIAL THROUGH INTERACTIVE METHODS IN THE SUBJECT OF EDUCATION - Novshadbekova Dilnura Zafarbek qizi (The Conference Hub, 2025)
This article explores the theoretical and practical aspects of developing students’ intellectual potential through the use of interactive methods in teaching the subject of education. Interactive methods are analyzed as an effective form of organizing the learning process based on a learner-centered approach, active participation, and independent thinking.
Keywords: Education subject, interactive methods, intellectual potential, pedagogical technology, creative thinking, problem-based learning, learner-centered approach, quality of education, reflection, critical thinking.